PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA PELAJARAN FISIKA POKOK BAHASAN FLUIDA DINAMIS UNTUK SMA KELAS XI - Syukron Khamzawi; Ketang Wiyono; Zulherman Zulherman (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2015)
This study aims to produce interactive multimedia-based learning model ProblemBased Learning (PBL) in the physics subject of fluid dynamic valid, practical, and knowing itspotential effects. The method used is a research development (development research) withmeasures Akker research development which consists of four stages: (1) the stage ofpreliminary examination; (2) the stage of theoretical adjustment; (3) empirical testing phase,and (4) the stage of documentation, analysis, and reflection on the process and results. At thisstage of empirical test using Tessmer formative evaluation model which consists of five stages:(1) self-evaluation; (2) expert reviews; (3) one-to-one evaluation; (4) small group; and (5)field test. The instrument used in this study is the validation sheet, interview, questionnaire,and achievement test. This research has produced an interactive multimedia PBL valid with apercentage score of validity of the product obtained from the validator of 92.75% with a veryvalid category. Interactive multimedia PBL has a percentage score practicality of the productobtained in small group step amounted to 81.15% with the category of very practical. N-Gainobtained in field test step of 0.4 with medium category. Based on the research results, it can beconcluded that the interactive multimedia-based learning model Problem Based Learning(PBL) in physics subject of fluid dynamic developed has met the criteria of validity andpracticality as well as having a potential effect on learning outcomes of students with moderatecategory.